Contamination of spices with moulds potential producers of sterigmatocystine - Kocić-Tanackov Sunčica D.; Dimić Gordana R.; Karalić Dragana (Acta Periodica Technologica, 2007)
The presence of moulds, potential producers of sterigmatocystine, was investigated in 20 samples of spices (cinnamon, caraway, marjoram and clove). The following five species were isolated from the samples: Aspergillus versicolor, Aspergillus sydowii, Aspergillus ustus, Emericella nidulans and Eurotium herbariorum. E. herbariorum was present in all the investigated spice samples, accounting for 7.6% of total mycopopulation in caraway and 42.9% in cloves. A. versicolor was detected in cinnamon, caraway and marjoram, accounting for 0.4% of total mycopopulation in caraway and 1.5% in cinnamon; A. ustus accounted for 0.1% of total mycopopulation in caraway and 0.4% in marjoram, while A. sydowii accounted for 18.9% of total mycopopulation in marjoram and 7.1% in clove. E. nidulans was a contaminant of caraway (0.01%) and marjoram (0.4%). .